Penerapan Keberlanjutan Operasional Perusahaan Pailit dalam Perspektif Hukum Kepailitan di Indonesia - Mamusung, Louis Z.; Gunadi, Ariawan (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 13 No 4 (2024), 2024)
The research objective of this article is to evaluate whether bankruptcy law policies in Indonesia are adequate in supporting operational sustainability and recovery of bankrupt companies and to analyze the role of curators and commercial courts in the operational sustainability process of bankrupt companies. The research method used in this article is a normative legal research method with a statutory approach and a conceptual approach. The research results show that bankruptcy law policy in Indonesia is inadequate and still has many shortcomings in supporting the recovery and operational sustainability of bankrupt companies. Policy reform is needed so that the focus can shift from liquidation to restructuring, taking into account the interests of all parties. This will create a more supportive environment for companies to recover and resume operations. The role of curators and commercial courts is very important in determining the continuity of company operations after the bankruptcy decision. The curator acts as a manager who ensures that the company's assets can be utilized as optimally as possible, while the commercial court provides legal supervision and approval of these sustainability measures. In this way, both parties collaborate to achieve the main objective of the bankruptcy process, namely providing the best solution for all interested parties, whether through debt repayment or potential company recovery.